FEATURES OF THE DEVELOPMENT AND DESIGN OF SUB-GAS OIL DEPOSITS IN UZBEKISTAN - Bobomurodov Utkir Ziyadullayevich (Scientific Trends, 2024)
In the process of drilling production wells, it is important to choose the right type and volume of drilling fluids, the correct choice of well bottom design, not to pollute the productive formation and maintain its natural permeability, and to effectively open the productive formation. Methods and drilling of wells Ensuring long-term production is one of the most pressing issues today
Keywords: Oil, gas, reservoir, well, geological, drilling, deformation, perforation, repression, productivity